The Role of Mothers in Early Childhood Education amidst the COVID-19 Pandemic in Indonesia (PIAUD IAIN Kudus, 2022)
The spread of COVID-19 impacted education sector in which teachers cannot carry out the face-to-face (offline) learning. Consequently, teaching and learning activities are conducted online which students access from home with the help of their main carers especially mothers. This study aims to explore the role of Indonesian mothers in their early childhood education amidst the COVID-19 pandemic. It reports challenges experienced by mothers in accompanying their children’s online study from home. Data were collected from semi-structured interviews with six Indonesian mothers. The study finds that the roles of mothers to their children’s online learning include providing the children’s needs in online classes, assisting children to do the assignments, managing time between house chores and kid’s schooling, and concerning for mental kid’s health and families. It is clear that Indonesian moms encountered myriad of challenges during their children’s online class in the COVID-19 pandemic time. These challenges were worsened by the lack of technical expertise, lack of training and support, lack of preparation among children, difficulties in managing the time between children’ school and other works, and problems with internet connection. This study proposes an involvement and collaboration between parents, so that online learning can be facilitated by both fathers and mothers. This collaboration is needed to ensure the successful online learning for the children, especially during the COVID-19 pandemic.